PELATIHAN PENELITIAN TINDAKAN KELAS/PTK (CLASSROOM ACTION RESEARCH) GURU-GURU SLB/B TABANAN - I G. A.M, SRINADI; NILAKUSMAWATI, D. P. E. (Buletin Udayana Mengabdi, 2012)
ABSTRACT Classroom Action Research/PTK can be done as class or school problem solving. With PTK, school education obtained the practical benefit including the mistakes of concept in subject and the teacher’s difficulties on learning. The aimed of this Community service was to introduce the basic concept and the execution procedure of classroom action research for the SLB/B Tabanan teachers. This training also improved their knowledge and skill of classroom action research. Based on the pre test, from 30 teachers as the participant of the training, there was a teacher in the good category, 17 teachers in the fairly good category and 12 in the poor category. By the end of the training, the post test descriptively showed that after attending this training there were no longer teacher in the poor category, 13 teachers in the fairly good category and 17 in the good category.